Listening anxiety from Saudi EFL learners' perspectives - Oteir, Ibrahim Naser (2018)
Listening skill is essential for effective communication. Studies have shown that English as a Foreign Language (EFL) learners experienced listening anxiety when dealing with English listening tasks or activities. In spite of listening anxiety being extensively studied in different parts of the world, listening anxiety in Arab countries remains unexplored. Therefore, this qualitative case study was conducted with the following objectives: a) to explore the causes of listening anxiety, b) to understand the effects of listening anxiety, and c) to identify the strategies that the Saudi EFL learners used to overcome their listening anxiety. This study was guided by Wheeless‟s Receiver Apprehension, Maclntyre‟s Recursive Relations Model and Inverted-U Model. Data were gathered from 15 students and five lecturers through two data collection techniques which were interviews and document analysis. The data were analyzed using thematic analysis. The study revealed that the causes of listening anxiety from the students‟ perspectives were related to the problematic nature of listening, the types of question or topic, the low English language proficiency of the students, cultural differences and the classroom environment. The study also found three types of effects pertaining to listening anxiety, which are personal effects, social effects and academic effects. With regard to the strategies used by the students to reduce listening anxiety, four main strategies found were cognitive strategy, metacognitive strategy, affective strategy and memory strategy. This study can help EFL learners reduce the level of anxiety in listening classes by using certain listening strategies and can also enrich understanding about the effects of listening anxiety. Furthermore, this study helps to improve the teaching of listening skill. It also suggests that the Ministry of Education in Saudi Arabia introduces the teaching of listening at school level.